Ethnogenèse du New Age andin : à la recherche de l’Inca global - Antoinette Molinié (Journal de la Société des Américanistes)
Ethnogenesis of the Andean New Age: in search of the global Inca. In Peru, we witness the emergence of an original culture that takes its roots from two matrices: the Andean culture that results from a fusion of the pre-Hispanic culture with Christianism, and the New Age movement that has been introduced with mystic tourism. The fusion of these two strands gives rise to ritual creations that we describe and analyze. Through ethnographical observations, we have identified some of the inventive procedures of this new tradition. The neo-Incas have given an imperial pre-Hispanic dimension to indigenous cults. The State Indian has offered a model of autochtony to the Peruvian nation. The New Agers movement have borrowed from neo-Indian representations and grafted their own concepts on them. In this manner, the world-wide popularization of a tradition is not introduced through some theoretical debate on the way cultures tend to dissolve in globalization, but through the analysis of ethnographic data.